Combined association of gait speed and processing speed on cardiometabolic disease mortality risk in the US older adults: a prospective cohort study from NHANES - Yang, Hang; Zhou, Ye; Wang, Xiaoying; Xu, Xiaoming (Frontiers in Aging Neuroscience, 2025)
BackgroundGait speed and processing speed, as measured by the Digit Symbol Substitution Test (DSST), are important indicators of health in older adults, with their potential impact on mortality risk. However, their combined effects on cardiometabolic disease (CMD) mortality remain unclear.ObjectiveThis study investigates how gait speed and cognitive function, individually and combined, influence CMD-specific and all-cause mortality in older adults.MethodsData were obtained from the National Health and Nutrition Examination Survey 1999–2002, with mortality follow-up linked to the National Death Index. Gait speed was measured by the timed 20-foot walk and processing speed was assessed using the DSST. Then the combined Gait-DSST groups were created and the Cox proportional hazards regression (HR) models were applied to examine their associations on CMD-specific and all-cause mortality, as well as the subgroup analyses stratified by age, sex and education.ResultsA total of 2,482 participants aged ≥60 years were included in the study with a median follow-up of 175 months, during which 587 CMD-specific deaths and 1,627 all-cause deaths were recorded. The slow gait was significantly associated with increased risk of CMD mortality, while low processing speed was only significantly associated with increased all-cause mortality risk. When analyzing the combined groups, individuals with slow gait and high processing speed exhibited a 86% increased risk of CMD mortality (HR = 1.86, 95% CI: 1.29, 2.68). However, the group with poor gait and processing speed had a twofold increased risk for all-cause mortality (HR = 2.01, 95% CI: 1.69, 2.39). The significant associations between slow gait with low processing speed and CMD mortality was more likely to be in age<75 years, male, and less-educated populations.ConclusionSlow gait is a significant predictor of CMD-specific mortality in older adults, largely independent of processing speed. Routine screening of gait speed and DSST performance should be prioritized in clinical and public health settings. Future intervention studies should aim at elucidating the biological and behavioral mechanisms linking physical and cognitive function to CMD outcomes.